Penerapan Politik Kriminal dalam Penanggulangan Tindak Pidana Terorisme - Ryan Aditama (Wajah Hukum, 2019)
The application of criminal politics in the handling of criminal acts of terrorism is a preventive measure that can be taken to reduce the crime rate of terrorism. Terrorism is an organized crime, has a national and international network that is very troubling and concerns the world. Criminal acts of terrorism will occur at any time with unpredictable targets, their actions cause widespread public fear, cause casualties and property losses that are not small, also cause a very broad impact on the life of nation and state. Considering that the crime of terrorism is an extraordinary criminal act, it will also be overcome by using unusual methods such as ordinary crime in general. The preservation of criminal politics is a preventive effort that can be carried out by the government in preventing the emergence of criminal acts of terrorism.